O Movimento da Política de Formação Continuada “PNAIC”: do documento oficial aos professores alfabetizadores - Felix, Carla Fernanda Figueiredo (2020)
Teacher’s continuing formation is one of the focus of educational policies. It has an assumption of improving the teaching quality, the teaching practice, and its professionalization. One specific program is evidenced in this research, the “Pacto Nacional de Alfabetização na Idade Certa” – PNAIC. To understand and problematize how this proposal, elaborated by the federal government, was structured, was implemented and developed, thinking about the recontextualization movement that goes from the official document to the study advisors and from these to the literacy teachers in Poços de Caldas, Minas Gerais, is the objective of this study. In this perspective, the guiding question was: how were the orientations about continuing formation from PNAIC recontextualized by the study advisors and literacy teachers? To accomplish that some strategies were used when collecting the data, in a qualitative approach, such as the gathering of the base documents of the proposal, making questionnaires and semi-structured interviews with teachers and study advisors. To process the material, an analytical model based on Basil Bernstein’s theory (1996) about the recontextualization of the pedagogic speech, listing four fronts: the formation dynamics; the aspects that had the biggest impact on teachers and study advisors from the formative point of view.; the base material for PNAIC, highlighting the perception both groups had about them; and the continuing formation conception built after the formation ended. Divided in four sections, this text presents on the first the methodological paths assumed in the research, anchored on the studies of Bogdan and Biklen (2013), Lüdke and André (2014) and Martins (2010). The educational policies and the continuing formation of teachers are topics described in the second section, using as basis the studies of Gatti (2008;2010), Gatti and Barreto (2009), Dourado (2007;2015;2016), Freitas (1992;2011;2014), Imbernón (2009;2010;2011) and Saviani (2008a; 2008b). The third section presents and analyzes the structure and reference books of PNAIC from Bernstein’s (1996) theoretical perspective about code, pedagogic recontextualization, framing and classification. Finally, the last section presents data from the questionnaire and semi-structured interview using Bernstein’s (1996) analytical model, adding to the discussion thoughts on teacher knowledges, assuming as reference Tardif’s (2010) and Tardif and Lessard’s (2014a; 2014b) studies. In that way, this research puts that, by means of the pedagogic recontextualization of the instructions provided by the continuing formation proposal from PNAIC, the subjects assume resistance postures when facing the official discourse, acting also as producers and not only reproducers of specific knowledges pertaining the complexity that involves the teaching practice.